2007
DOI: 10.1007/s10461-007-9245-4
|View full text |Cite
|
Sign up to set email alerts
|

Popular Use of Traditional Chinese Medicine in HIV Patients in the HAART era

Abstract: Seventy-six Chinese male HIV patients were interviewed on their use of traditional Chinese medicine (TCM). All except one had undetectable viral load, 28 had already progressed to AIDS. Forty-five (59.2%) had used TCM--11 infrequently and 33 commonly. No specific TCM recipe was preferentially used, while a variety of herbal tea and other over-the-counter health products of TCM in origin were reported. A minority (28.9%) have consulted a TCM practitioner in the preceding 6 months. Most patients admitted using T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…This prevalence rate of CM use is somewhat lower than that observed in other commonly occurring chronic conditions in Chinese communities [17][19]. In non-CM-using patients, nearly 58% did not believe CM could help their condition, suggesting that the lower prevalence of CM use in schizophrenic population is mainly related to their negative attitude towards this traditional remedy.…”
Section: Discussionmentioning
confidence: 59%
“…This prevalence rate of CM use is somewhat lower than that observed in other commonly occurring chronic conditions in Chinese communities [17][19]. In non-CM-using patients, nearly 58% did not believe CM could help their condition, suggesting that the lower prevalence of CM use in schizophrenic population is mainly related to their negative attitude towards this traditional remedy.…”
Section: Discussionmentioning
confidence: 59%
“…A study done in China on seventy-six male HIV patients on use of traditional Chinese medicine showed that all except one had achieved undetectable viral load [21]. …”
Section: Discussionmentioning
confidence: 99%
“…In 2005, a survey in Hong Kong showed that 59.2% of HIV/ AIDS patients use TCM, most patients using TCM for treatment of a minor illness (60.0%) and general healthcare (57.8%), while they chose western medicine for therapy of important disease [60].Although numerous studies have shown the efficacy of TCM for prevention of HIV infection and treatment of AIDS patients, few of these studies were strictly designed, and the evidence was inadequate. Also, some people doubted that whether there were any inhibitors for treatment of AIDS patients from Chinese's herbs.…”
Section: Summary and Perspectivesmentioning
confidence: 99%